Fracture vascularity and bone healing: a systematic review of the role of VEGF. - Keramaris, N C; Calori, G M; Nikolaou, V S; Schemitsch, E H; Giannoudis, P V (Injury, 2008)
SUMMARY: Fracture healing constitutes a complex and delicate physiological process. Local vascularity at the site of the fracture has been identified as one of the most significant parameters influencing the healing procedure. VEGF is the most important component of the regeneration of the vascular system at the fracture site. The aim of this review is to determine the evidence supporting the direct role of VEGF in the enhancement of fracture healing and the possible clinical use of VEGF for non-unions. The literature search was performed via the internet using the Medline. The key words which were searched in the abstracts were the terms "VEGF", "angiogenesis", "fracture", "bone" and "healing". Twenty-five articles were relevant to the topic of interest. A total of 11 articles were excluded from our research due to non conformity of their content to the inclusion criteria. Evidence retrieved suggests that VEGF could be extremely valuable for the treatment of critical size bone defects and that VEGF could have a direct effect on osteoprogenitor cells, mainly by promoting the differentiation of osteoblasts and by increasing the mineralisation of the regenerated bone. The former observation could have very interesting repercussions for the field of non-unions and the latter for the field of osteoporosis.
Keywords: Animals; Bone and Bones; Fracture Healing; Fractures, Bone; Fractures, Ununited; Gene Transfer Techniques; Genetic Therapy; Humans; Mice; Neovascularization, Physiologic; Rabbits; Rats; Vascular Endothelial Growth Factor A